Alienation : individual or social problem? - Urick, Ronald V. (Englewood Cliffs, N.J. : Prentice-Hall, 1977)
A high school textbook defining alienation with a discussion of its causes and possible methods of coping with this problem
Bibliography : p. 113-117
Keywords: Alienation (Social psychology); Social isolation; United States -- Social conditions -- 1960-1980